AB1234 Clinical characteristics of IgG4-related orbital pseudo-tumor. (23rd January 2014) - Origuchi, T.; Kawashiri, S.-Y.; Ichinose, K.; Tamai, M.; Arima, K.; Yamasaki, S.; Nakamura, H.; Kawakami, A.
Abstract : Background: IgG4-related disease (IgG4-RD) is a new emerging disease entity of unknown etiology with multiorgan involvement. IgG4-RD includes a wide variety of diseases, including Mikulicz's disease (MD), autoimmune pancreatitis (AIP), hypophysitis, Riedel thyroiditis, interstitial pneumonitis, interstitial nephritis, prostatitis, lymphadenopathy, retroperitoneal fibrosis, inflammatory aortic aneurysm, and inflammatory pseudo-tumor. It was thought that almost orbital pseudo-tumors were idiopathic except malignant lymphoma. However, recently, IgG4-RD was suspected to be an origin of orbital pseudo-tumor. Objectives: We clarified the characteristics of IgG4-related disease manifested by orbital pseudo-tumor. Methods: We examined three cases of IgG4-related orbital pseudo-tumor. We summarized the radiographic and pathological characteristics of IgG4-related orbital pseudo-tumor. Results: Patients were 64-75 year-old men. They noticed a mass lesion in an upper eyelid and received an operation for the removal of the mass. A histopathological examination revealed the accumulation of IgG4 positive plasma cells (IgG4/IgG ratio:40.0-51.1%). The serum level of IgG4 was 178-666mg/dl. MRI revealed low T1 intensity and low T2 intensity in three cases. In one case, Gallium scintigraphy showed hot spots in right parotid gland, bilateral submandibular glands, neck and hilar lymph nodes. And in another case, it showed an accumulation in bilateral hilar lymph nodes, right side of thoracic vertebrae and ileocecum. Conclusions: We found three IgG4-related diseases in the cases who had orbital mass lesions. We also suggested that a histopathological examination and serum IgG4 concentration were important for the diagnosis of IgG4-related disease in orbital mass lesions. References: Masaki Y, Dong L, Kurose N, et al. Proposal for a new clinical entity, IgG4-positive multiorgan lymphoproliferative syndrome: analysis of 64 cases of IgG4-related disorders. Ann Rheum Dis. 2009 68(8):1310-5. Disclosure of Interest: None Declared